2003
DOI: 10.1108/02683940310494359
|View full text |Cite
|
Sign up to set email alerts
|

Work stress, control beliefs and well‐being in Greater China

Abstract: Towards the end of the twentieth century, the world has witnessed an amazing economic take‐off in the East Asia, especially within the territory of so‐called “Greater China”, encompassing the PRC and Taiwan. Against this economic and cultural background, this study surveyed 258 and 189 employees respectively in Taiwan, and the PRC (Shanghai), to examine generalizability of a generic work‐stress model to the Chinese societies. It further examined the sub‐cultural differences in the work‐stress processes, by dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 46 publications
4
35
0
1
Order By: Relevance
“…Chinese coping strategies such as seeking social support and active action were positively related to job performance. These findings were consistent with previous studies showing detrimental effects of work stressors and beneficial effects of coping separately for the Chinese people (e.g., Lu, 1997, 1999; Lu et al, 2001, 2003; Siu et al, 2006). The added value of the present study is that we included subsamples from three geographical subregions in the Greater China zone—mainland China, Hong Kong and Taiwan—thus our current pooled sample better represents Chinese employees in the region.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Chinese coping strategies such as seeking social support and active action were positively related to job performance. These findings were consistent with previous studies showing detrimental effects of work stressors and beneficial effects of coping separately for the Chinese people (e.g., Lu, 1997, 1999; Lu et al, 2001, 2003; Siu et al, 2006). The added value of the present study is that we included subsamples from three geographical subregions in the Greater China zone—mainland China, Hong Kong and Taiwan—thus our current pooled sample better represents Chinese employees in the region.…”
Section: Discussionsupporting
confidence: 93%
“…Twenty‐three items were chosen from existing Western scales that have also been found relevant to the Chinese and proved reliable (Liu, 2002; Lu, 1997, 1999; Lu et al, 2001, 2003). We used these items to assess four stressors: workload (5 items; Spector & Jex, 1998, e.g., “How often is there a great deal to be done?”), organizational constraints (11 items; Spector & Jex, 1998, e.g., “lack of equipments or supplies”), interpersonal conflict (4 items; Spector & Jex, 1998, e.g., “How often are people rude to you at work?”), and lack of autonomy (3 items; Hackman & Oldham, 1975; e.g., “I decide on my own how to go about doing the work”, reversed score).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al . () found that in workplaces in Taiwan, China and Hong Kong, the poorer mental health indicated by the research subjects was mostly related to a high perception of pressure. Other studies have also found a significant negative correlation between perceived stress and mental health (Elkins et al .…”
Section: Literature Reviewmentioning
confidence: 91%